2017
DOI: 10.1016/j.redox.2016.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Neuroprotective action of N-acetyl serotonin in oxidative stress-induced apoptosis through the activation of both TrkB/CREB/BDNF pathway and Akt/Nrf2/Antioxidant enzyme in neuronal cells

Abstract: N-acetyl serotonin (NAS) as a melatonin precursor has neuroprotective actions. Nonetheless, it is not clarified how NAS protects neuronal cells against oxidative stress. Recently, we have reported that N-palmitoyl serotonins possessed properties of antioxidants and neuroprotection. Based on those, we hypothesized that NAS, a N-acyl serotonin, may have similar actions in oxidative stress-induced neuronal cells, and examined the effects of NAS based on in vitro and in vivo tests. NAS dose-dependently inhibited o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
114
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 158 publications
(129 citation statements)
references
References 24 publications
(57 reference statements)
6
114
0
Order By: Relevance
“…Concerning the structural importance of N ‐acyl serotonins, the neuroprotective activity of Pal‐5HT may be correlated with the length and polarity of aliphatic acyl chain. In support of this, Pal‐5HT exerted stronger neuroprotective activity than other N ‐acyl serotonins such as N ‐stearoyl serotonin and N ‐docosahexaenoyl serotonin in oxidative stress‐exposed neuronal cells, and N ‐acetyl serotonin possessed neuroprotective action in in vitro and in vivo studies . However, its effect was inferior to that of Pal‐5HT .…”
Section: Discussionmentioning
confidence: 62%
See 2 more Smart Citations
“…Concerning the structural importance of N ‐acyl serotonins, the neuroprotective activity of Pal‐5HT may be correlated with the length and polarity of aliphatic acyl chain. In support of this, Pal‐5HT exerted stronger neuroprotective activity than other N ‐acyl serotonins such as N ‐stearoyl serotonin and N ‐docosahexaenoyl serotonin in oxidative stress‐exposed neuronal cells, and N ‐acetyl serotonin possessed neuroprotective action in in vitro and in vivo studies . However, its effect was inferior to that of Pal‐5HT .…”
Section: Discussionmentioning
confidence: 62%
“…In support of this, Pal‐5HT exerted stronger neuroprotective activity than other N ‐acyl serotonins such as N ‐stearoyl serotonin and N ‐docosahexaenoyl serotonin in oxidative stress‐exposed neuronal cells, and N ‐acetyl serotonin possessed neuroprotective action in in vitro and in vivo studies . However, its effect was inferior to that of Pal‐5HT . Besides, lipid‐soluble molecules are known to have higher cell‐membrane permeability than polar molecules .…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…By activating the IP3K/Akt kinase pathway, neurotrophins inhibit processes that elicit cell death [55][56][57]. It was found that the decrease in expression of NTs, especially BDNF observed in the aging process and in neurodegenerative diseases, may contribute to degeneration and death of neurons [58].…”
Section: Role Of Bdnf In Neurodegeneration and Neuroregenerationmentioning
confidence: 99%
“…Activated CREB promotes the expression of brain-derived neurotrophic factor (BDNF) (Yoo et al, 2017), while on the other hand, BDNF promotes the activation of CREB through tropomyosin receptor kinase (Trk) B receptors (Finkbeiner et al, 1997). Direct relationships were also found between antipsychotic drugs binding to D2R, therapeutic effect, and stimulation of CREB phosphorylation in vitro and in animal models (Konradi et al, 1993; Lee et al, 2010).…”
Section: Introductionmentioning
confidence: 99%